A semi-empirical model for predicting yielding in metallic glass matrix composites. (September 2019) - Li, H.Y.; Qiao, J.W.; Wang, Z.; Shi, X.H.; Yang, H.J.; Wu, Y.C.
Abstract: Macroscopic yielding is essentially important in structural application. In this study, a wisdom semi-empirical model, based on the rule of mixture (RoM), has been proposed to predict the yielding strength in in-situ metallic glass matrix composites (MGMCs). The present model not only successfully predicts the yielding strength of a variety of dendrite-reinforced MGMCs, but also can be verified in bimetal alloys or composites with different systems. A quantitative relationship between the specific strength and shear velocity in metallic materials was established, which provides a guidance for the development of light-weight and high-strength MGMCs. Graphical abstract: Unlabelled Image